Rumen Fungi and Forage Fiber Degradation - Windham, W. R. (1984)
The role of anaerobic rumen fungi in in vitro forage fiber degradation was determined in a two forage × two inoculum source × five treatment factorial design. Forages used as substrates for rumen microorganisms were Coastal bermuda grass and alfalfa; inoculum sources were rumen fluid samples from a steer fed Coastal bermuda grass hay or alfalfa hay; treatments were whole rumen fluid (WRF), WRF plus streptomycin (0.2 mg/ml of rumen fluid) and penicillin (1.25 mg/ml of fluid), WRF plus cycloheximide (0.5 mg/ml of fluid), WRF plus streptomycin, penicillin, and cycloheximide, and McDougall buffer. Populations of fungi as shown by sporangial development were greater on bermuda grass leaves than on alfalfa leaflets regardless of inoculum source. However, endogenous fungal populations were greater from the alfalfa hay inoculum. Cycloheximide inhibited the fungi, whereas streptomycin and penicillin, which inhibit bacterial populations, resulted in an increase in numbers of sporangia in the alfalfa inoculum, suggesting an interaction between bacteria and fungi. Bacteria (i.e., WRF plus cycloheximide) were equal to the total population in degrading dry matter, neutral-detergent fiber (NDF), acid-detergent fiber (ADF), and cellulose for both inocula and both forages. Degradation of dry matter, NDF, ADF, and cellulose by anaerobic fungi (i.e., WRF plus streptomycin and penicillin) was less than that due to the total population or bacteria alone. However, NDF, ADF, and cellulose digestion was 1.3, 2.4, and 7.9 percentage units higher, respectively, for bermuda grass substrate with the alfalfa versus bermuda grass inoculum, suggesting a slight benefit by rumen fungi. No substantial loss of lignin (72% H(2)SO(4) method) occurred due to fungal degradation. The most active fiber-digesting population in the rumen was the bacteria, even when streptomycin and penicillin treatment resulted in an increase in rumen fungi over untreated WRF. The development of large numbers of sporangia on fiber may not indicate a substantial role as digesters of forage.